RESTRUCTURING OF RAT LUNGS IN ACUTE IMMOBILIZATION STRESS AND ITS CORRECTION - Yeroshenko, G.А.; Koptev, М.М.; Bilash, S.М.; Shevchenko, K.V.; Yachmin, А.І. (World of Medicine and Biology, 2019)
Currently, the search for advanced effective and safe methods of preventing and treatment of stress disorders is one of the priority tasks of medical science. The paper was aimed at the morphological study of the corrective effect of torasemide on rat lungs in experimental acute immobilization stress compared to the stress-protective effect of mexidol. Taking into account the norms of bioethics, the study was involved 30 mature albino male rats. Group І (controls) (n=10) involved animals, exposed to stress without correction; Group II (n=10) involved rats, exposed to stress after administration of mexidol; Group III (n=10) involved rats, exposed to stress that was corrected with torasemide. Correction with pharmacological drugs, especially torasemide, reduces stress effect on the lungs. Histologically, torasemide contributes to retention of the epithelial lining integrity, local visualization of intra-alveolar erythrocytes, and plethora in the capillaries of the interalveolar septa. In the epithelial lining of the bronchi, desquamation of individual cells was sometimes observed. The findings of the study have shown that torasemide has a pronounced stress-protective effect on the lung tissue, which is more powerful than correction with mexidol.
Keywords: lungs; stress; correction; torasemide; mexidol; morphology